RETRACTED: Numerical study of particle motion in a two-dimensional channel with complex geometry - Ibrokhimov Abdulfatto; Djumaev Khikmatilla; Artikova Bakhtigul; Abdukadirov Farkhod (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001